Improved Steepest Descent Method using Modified Bessel Function K_(1/4 ) for Gamma Function Evaluation - Adam Badra Cahaya (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2021)
Steepest descent method employs a Gaussian function when approximating an integral of a function. In this article we improve the approximation by using function in the form of . As an example, we approximate the value of gamma function to provide improved approximation for Stirling formula that is often used for estimating factorial of a large number.